2012
DOI: 10.1258/jtt.2012.110704
|View full text |Cite|
|
Sign up to set email alerts
|

Using preventive home monitoring to reduce hospital admission rates and reduce costs: a case study of telehealth among chronic obstructive pulmonary disease patients

Abstract: We studied whether preventive home monitoring of patients with chronic obstructive pulmonary disease (COPD) could reduce the frequency of hospital admissions and lower the cost of hospitalization. Patients were recruited from a health centre, general practitioner (GP) or the pulmonary hospital ward. They were randomized to usual care or tele-rehabilitation with a telehealth monitoring device installed in their home for four months. A total of 111 patients were suitable for inclusion and consented to be randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
19

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 10 publications
1
110
0
19
Order By: Relevance
“…122 Patients were recruited from a health center, a general practice, and a pulmonary hospital ward. Both intervention and control groups were observed over a 10-month period.…”
Section: Effects Of Telepulmonology On Use Of Servicementioning
confidence: 99%
“…122 Patients were recruited from a health center, a general practice, and a pulmonary hospital ward. Both intervention and control groups were observed over a 10-month period.…”
Section: Effects Of Telepulmonology On Use Of Servicementioning
confidence: 99%
“…Данная рекомендация основана на РКИ [118][119][120], проанализированных в систематическом обзо ре [121], и дополнительных РКИ [122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139]. Из них только 6 исследований были объединены для данной рекомендации [127,[130][131][132][133][134], хотя эксперты также принимали во внимание и результаты других иссле дований, не включенных в метаанализ.…”
Section: клинические рекомендацииunclassified
“…A meta-analysis examining 80 studies suggested that there is no conclusive evidence that such interventions are cost effective (Mistry, 2012). Another study suggested that remote monitoring was not cost effective in reducing hospital costs in patients with chronic obstructive pulmonary disease (Dinesen et al, 2012).…”
Section: Cost and Millmentioning
confidence: 99%